SÊRAT DARMASUNYA MACAPAT DAN KAKAWIN DHARMA ŚŪNYA DALAM HUBUNGAN TRANSFORMASI - Wiwien Widyawati Rahayu (Humaniora, 2015)
Studies on Sêrat Darmasunya are conductedthrough literary and philological research. This is because both types of the studies cannot be absolutely separated. Sêrat Darmasunya is a holistic structure. Every element with a particular situation does not have a meaning in itself but,rather, the meaning is determined by its relationships with the other elements involved. A full meaning can be comprehended only if this element is integrated into the structure that is the overall elements. As a macapat song or a Javanese poetry, Sêrat Darmasunya should be understood by paying attention to the relationships between its elements as a part of the whole structure. The structure of Sêrat Darmasunya should be analyzed based on the constituent elements of a poetry. These elements comprise intrinsic and extrinsic elements. Then, the critical edition of Serat Darmasunya was then analyzed through the approach of Intertextual-transformation theory. Sêrat Darmasunya provides information that between the manuscript and the text under study have similar contents. Although written with different metrum and in different languages, there are similarities in both explicit and implied meaning. Cultural environment shaped the mindset of the authors, whocame from the same environment that was the acculturation environment between Hindu and Javanese culture